Modelling and optimal control for two- wheeled self-balancing robot - Nguyen , Minh Tâm; Nguyen , Văn Đông Hải; Nguyen , Phong Lưu; Le , Văn Tuấn (Journal of Technical Education Science, 2016)
Two-wheeled Self-balancing Cart is a popular model in automatic experiments. This is a MIMO system (multi-input and multi-output) which is theoretical, practical and has been applied in normal life. Anyway, most research just focuses on balancing this model through try-on experiments or simple form of mathematical model. There are still so few research works focusing on modelling algorithm and designing a mathematical model-based controller for this system. This paper developed all mathematical equations of the system. Then, the authors successfully applied optimal control for this system. Optimal controller was tested with different cases of cart motion. Controlling results was proved to work well through both experiments and simulation on Matlab/Simulink